Effects of occlusion pressure on hemodynamic responses recorded by near-infrared spectroscopy across two visits - Desanlis, Julien; Gordon, Dan; French, Chloe; Calveyrac, Camille; Cottin, François; Gernigon, Marie (Frontiers in Physiology, 2024)
Ischemic Preconditioning (IPC) has emerged as a promising approach to mitigate the impact of hypoxia on physiological functions. However, the heterogeneity of occlusion pressures for inducing arterial occlusion has led to inconsistent hemodynamic outcomes across studies. This study aims to evaluate the peripheral hemodynamic responses to partial and total blood-flow occlusions on the left arm at rest, using absolute or individualized pressures, on two occasions. Thirty-five young males volunteered to participate in this study. IPC procedure (3 x 7-min) was performed on the left upper arm with cuff pressures at 50 mmHg (G1), 50 mmHg over the systolic blood pressure (SBP+50 mmHg) (G2) or 250 mmHg (G3). NIRS-derived parameters were assessed for each occlusion and reperfusion phase in the brachioradialis. Results showed a significantly lower magnitude of deoxygenation (TSIAUC) for G1 compared to G2 (-1959.2 ± 1417.4 vs -10908.1 ± 1607.5, P < .001) and G3 -1959.2 ± 1417.4 vs -11079.3 ± 1828.1, P < .001), without differences between G2 and G3. However, G3 showed a significantly faster reoxygenation only for tissue saturation index (TSIslope) compared to G2 (1.3 ± 0.1 vs. 1.0 ± 0.2, P = 0.010), but without differences in the speed of recovery of deoxyhemoglobin ([HHb]slope), or in the magnitude of post-occlusive hyperemia (PORH). Besides TSI reoxygenation speed, G2 and G3 elicit comparable resting hemodynamic responses measured by NIRS. Thus, this study highlights the practicality and effectiveness of using relative occlusion pressures based on systolic blood pressure (SBP) rather than relying on excessively high absolute pressures.